The Use of Concrete-Pictorial-Abstract Approach to Enhance Learners’ Conceptual Understanding of Fractions - Leboho Sello; Kgaladi Maphutha; Mutodi Paul (Edumatica: Jurnal Pendidikan Matematika)
In this paper, we explored how using the Concrete-Pictorial-Abstract (CPA) approach enhances learners’ conceptual understanding of fractions in the Capricorn North District of South Africa. The research is framed within the conceptual understanding theory rooted in cognitive constructivism. Conceptual learning is understanding mathematical ideas as an integrated and functional system with three components: comprehension, operations, and relations. A one-phase concurrent embedded mixed-method research design was used to gather qualitative data through task-based interviews and quantitative data through pretests and post-tests. Deductive thematic analysis was used to analyse the qualitative data. The quantitative data was analysed using descriptive statistics, independent and paired samples T-tests. Seventy (70) conveniently sampled Grade 7 learners participated in the study. The findings indicate that the CPA approach enhanced the learners’ conceptual understanding of fractions though the effect size of the intervention is minimal and negligible. Furthermore, the study found that the incorporation of concrete objects and visual aids proved to be efficient. Additionally, the qualitative results revealed how learners’ conceptual understanding of fractions was enhanced during the intervention. This study contributes to innovative teaching methods of fractions, potentially enhancing mathematics performance and inspiring educators to explore new teaching approaches.